Trabajo cooperativo y logros de aprendizaje en el área de comunicación en estudiantes del quinto ciclo de primaria de la Institución Educativa N° 61014 de Iquitos en el año 2024 - Rios Rioja de Cantoral, Gloria Luz (2025)
The central purpose of the present study was to determine the association existing between cooperative work and academic achievement in the subject of Communication, specifically among fifth-cycle primary education students at Educational Institution N° 61014 “Horacio Zevallos Gámez” in Iquitos, during the 2024 academic year. The research was based on a non-experimental design approach, with a nature that progressed from descriptive to correlational. The sample population consisted of 101 students. For data collection, a questionnaire was used, whose reliability and relevance were ensured through expert judgment for its validation. The inferential data analysis yielded a Spearman's Rho correlation coefficient of 0.452, accompanied by a significance level of p=0.000. These findings allow for the conclusion and demonstration that the variables cooperative work and learning achievements in the area of Communication, in the previously cited group of students, maintain a statistically significant and positive relationship.